Optimal Capital Structure for BOOT/BOT Model Hydropower Projects in Nepal - Gautam, Anup; Shrestha, Santosh Kumar (Journal of Advanced College of Engineering and Management, 2019)
Nepal has a huge hydropower potential which is yet to be developed. Hydropower are capital intensive infrastructure where financing from single source is not practical, so a financial mix is essential, i.e. debt and equity financing. Projects have been practicing different financial structures. Therefore a proper capital structure is necessary for maximizing return from the hydropower project. The main objective of this research is to determine the parameters that influence hydropower financing, collect data on parameters, analyze them and determine the optimal capital structure for hydroelectric projects in Nepal. The data of operating hydropower projects are collected from secondary sources mainly Department of Electricity Development, Nepal Electricity Authority and other published internet sources. The data is processed and financial analysis is performed for numerous cases using an excel sheet powered by visual basic application. The key parameters affecting hydropower financing are total project cost, annual generation (Dry and wet energy), interest on loan and interest on equity while other parameters are not frequently variable. The feasibility of the project is found to be greatly influenced by the cost of development and generation revenue. The optimal capital structure of hydropower projects is dependent on the key parameters. The cost of hydropower development in Nepal is found to be diverse with an average per megawatt cost of NRs. 219.2 million and standard deviation of NRs. 65.9 million. Energy generation varies from time to time and plant to plant with an average plant factor of 0.53 (Standard Deviation 0.20) out of which 33.16% is dry energy. The cost of loan varies from 8% to 12% and the cost of equity ranges 12% to 16%. The optimal capital structure for BOOT model hydropower projects in Nepal falls in the range of 11% to 34% with an expected value of 20.79%.